Non-genomic Actions of Thyroid Hormones Regulate the Growth and Angiogenesis of T Cell Lymphomas - Cayrol, Florencia; Sterle, Helena A.; Díaz Flaqué, Maria Celeste; Barreiro Arcos, Maria Laura; Cremaschi, Graciela A. (Frontiers in Endocrinology, 2019)
T-cell lymphomas (TCL) are a heterogeneous group of aggressive clinical lymphoproliferative disorders with considerable clinical, morphological, immunophenotypic and genetic variation, including approximately 10-15% of all lymphoid neoplasms. Several evidences indicate an important role of the non-neoplastic microenvironment in promoting both tumor growth and dissemination in T cell malignancies. Thus, dysregulation of integrin expression and activity is associated with TCL survival and proliferation .We found that thyroid hormones acting via the integrin αvβ3 receptor are crucial factors in tumor microenvironment affecting the pathophysiology of TCL cells. Specifically, TH-activated αvβ3 integrin signaling promoted TCL proliferation and induced and an angiogenic program via the up-regulation of the vascular endothelial growth factor (VEGF). This was observed both on different TCL cell lines representing the different subtypes of human haematological malignancy, and in preclinical models of TCL tumors xenotransplanted in immunodeficient mice as well. Moreover, development of solid tumors by inoculation of murine TCLs in syngeneic hyperthyroid mice, showed increased tumor growth along with increased expression of cell cycle regulators. The genomic or pharmacological inhibition of integrin αvβ3 decreased VEGF production, induced TCL cell death and decreased in vivo tumor growth and angiogenesis. Here we review the nongenomic actions of THs on TCL regulation and their contribution to TCL development and evolution. These actions not only provide novel new insights on the endocrine modulation of TCL, but also provide a potential molecular target for its treatment.